Considerations in the use of processing fluids for the detection of PRRSV RNA and antibody. (September 2022) - López, Will; Zimmerman, Jeff; Gauger, Phil; Harmon, Karen; Magtoto, Ronaldo; Bradner, Laura; Holtkamp, Derald; Zhang, Min; Zhang, Jianqiang; Ramirez, Alejandro; Linhares, Daniel; Giménez-Lirola, Luis
Surveillance is mandatory for tracking the progress of porcine reproductive and respiratory syndrome virus (PRRSV) control and elimination efforts in breeding herds. Processing fluids, the fluid recovered from tissues collected at castration and/or tail docking, are used for breeding herd surveillance by large segments of the industry, but the basic diagnostic characteristics of processing fluids are largely undescribed. We undertook 3 studies to address this information gap. In study 1, we found no differences among the PRRSV RT-rtPCR results obtained with 4 commercial RNA extraction kits. In study 2, we found that PRRSV RNA was highly stable in processing fluid samples at −20°C or 4°C, but detrimental effects were observed at ≥22°C within 24 h. In study 3, using a modified PRRSV ELISA at a sample:positive cutoff of ≥0.5, we found excellent discrimination in the detection of PRRSV antibody (IgM, IgA, IgG) in processing fluids from herds of known PRRSV status. Judicious handling of processing fluid samples from sow herds, and the use of methods available in veterinary diagnostic laboratories, can provide a foundation for reliable PRRSV surveillance.